Does macroprudential policy alleviate the adverse impact of COVID-19 on the resilience of banks? - Igan, Deniz; Mirzaei, Ali; Moore, Tomoe (Journal of Banking & Finance, 2023)
This paper examines the resilience of banks as perceived by market participants during the COVID-19 crisis. We analyse how bank stock returns during January-March 2020 relate to the pre-crisis activation of macroprudential policy across 52 countries in a cross-sectional dimension. We find that, overall, a tighter macroprudential policy stance is beneficial for bank systemic risk, as assessed by equity market investors. A robust finding is that a perceived decrease in bank risk stems primarily from the use of credit growth limits, reserve requirements, and dynamic provisioning. By contrast, a pre-crisis build-up of capital surcharges on systemically important financial institutions seems to lower bank stock returns. Alternative bank risk indicators suggest that the latter is likely to be driven by concerns about profits rather than the probability of default.